Numerical simulation of an array of droplets through a crossflow - Barata, Jorge M M (2012)
This paper describes the application of a three-dimensional computational method based on the solution of the Reynolds-averaged Navier-Stokes equations and a SSF (stochastic separated flow) model to the problem of an array of droplets through a crossflow. The calculation method is first evaluated against measurements for two-phase axisymmetric jets, and then extended to the three-dimensional case. The influence of the droplet sizes on the dispersion phenomena is analyzed. The exchange of momentum and turbulence energy was shown to play a decisive role in the change of the gaseous flow velocities. The analysis of the source terms due to the droplets revealed a strong influence of the boundary layer near the injection point in the dispersion process.